Activation of D1/5 Dopamine Receptors in the Dorsal Medial Prefrontal Cortex Promotes Incubated-Like Aversive Responses - Castillo Díaz, Fernando; Kramar, Cecilia P.; Hernandez, Micaela A.; Medina, Jorge H. (Frontiers in Behavioral Neuroscience, 2017)
It is well established that neurons of the mammalian medial prefrontal cortex (mPFC) modulate different behavioral outputs, including several memory types. This behavioral modulation is, at least in part, under the control of the D1-like dopamine receptor (D1/5R) which comprises D1 and D5-specific subtypes (D1R and D5R, respectively). Here, combining a set of behavioral assays with pharmacology we determined whether the activation of D1/5R in the mPFC during almost neutral or weak negative-valence experiences induces aversive behaviors. The intra mPFC bilateral infusion of the D1/5R agonist SKF 38393 (6.25 µg/side) immediately after exposing rats to the white compartment of a place conditioning apparatus promotes a incubated-like aversive memory when tested 7 days thereafter, but it was not seen 24 hours after conditioning. No signs of fear or changes in the anxiety state were observed after the exposure to the white compartment. This aversive response is observed only when the experience paired with the mPFC D1/5R activation has a context component involved. By using specific agonists for D1R or D5R subtypes we suggest that D5R mediate the induction of the aversive behavior. No aversive effects were observed when the D1/5R agonist was infused into the dorsal hippocampus (HP), the nucleus accumbens (NAcc) or the basolateral amygdala (BLA) of rats exposed to the white compartment. Taken together, our present findings endorse the idea that activation of mPFC D1/5R is sufficient to induce incubated-like aversive memories after exposing rats to an apparent neutral or weak negative-valence environment and that mPFC might be considered a key brain region involved in providing adaptive emotional behaviors in response to an ever-changing environment.